EVOLUTION OF THE CONCEPT OF THE "SILVER ECONOMY" - POKROVSKA, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The aim of the article is to summarize the global trends in the development of the concept of the "silver economy" and identify the key factors that shape its content in modern socio-economic conditions. It is established that the increase in average life expectancy, which has been observed since the second half of the 20th century, has significantly changed the structure of the population and caused an increase in the share of people aged 60+. Such demographic dynamics have led to the emergence of new challenges for social protection systems, healthcare and the labor market, while creating significant economic potential for the development of new market segments. In many countries of the world, including the EU, the USA and the countries of the Asia-Pacific region, a comprehensive policy of responding to demographic aging is gradually being formed, which includes the development of innovations, adaptation of social systems and stimulation of economic activity of older people.It is proven that the “silver economy” is turning into an independent direction of economic policy, focused on the development of the sectors of medical care, care, financial services, age-friendly infrastructure, digital technologies and new employment formats. The outlined processes form a growing global market of goods and services, which is already estimated at trillions of dollars and demonstrates high investment potential. In Europe, the USA, Japan and China, innovative models of longevity are being actively implemented, combining economic interests with the needs of older people. It is determined that the further direction of research into the concept of the “silver economy” requires a systemic approach aimed at integrating older citizens into socio-economic life, stimulating entrepreneurship, digital inclusion, developing modern medical and social services, as well as creating conditions for active and healthy longevity.
Keywords: silver economy; aging population; demographic changes; innovation; digitalization; SENER; active longevity; healthcare system; human resource potential